Nanowire Y-junction formation during self-faceting on high-index GaAs substrates. Issue 29 (23rd March 2017) - Méndez-Camacho, R.; López-López, M.; Méndez-García, V. H.; Valdez-Pérez, D.; Ortega, E.; Benitez, A.; Ponce, A.; Cruz-Hernández, E.
Abstract : In this contribution, we report on the observation of high-order and bi-dimensional surface mechanisms that allows the self-assembling of an alternating array of straight and bifurcated nanowires. Abstract : A major current focus in nanotechnology is the precise control of the self-assembling of semiconductor structures at the nanometric level. Highly uniform structures such as quantum wires can now be fabricated from the self-assembly of nanometric facet arrays produced using high-index substrates and epitaxial techniques. However, the self-assembling of more complex nanostructures such as Y-junctions is a more involved problem, hindering potential technological applications and one-dimensional physics exploration. In this contribution, we report on the observation of high-order and two-dimensional mechanisms in the Molecular Beam Epitaxy growth of GaAs on (6 3 1) oriented GaAs substrates. These mechanisms allow the formation of a regular alternating pattern of bifurcated nanowires, the Y-junctions. The Y-junction/nanowire arrays have suitable dimensions to form a one-dimensional electron gas device by use of a modulation doping structure with a source, a drain, and gate electrodes. Finally, the potential use of the bifurcated structures for the exploration of one-dimensional transport and as a viable alternative to carbon nanotube Y-junctions is discussed.